Using terrestrial leeches to assess the genetic diversity of an elusive species: The Annamite striped rabbit Nesolagus timminsi. Issue 4 (12th February 2021) - Nguyen, Thanh V.; Tilker, Andrew; Nguyen, An; Hörig, Lisa; Axtner, Jan; Schmidt, Anke; Le, Minh; Nguyen, Anh H. Q.; Rawson, Benjamin M.; Wilting, Andreas; Fickel, Joerns
Abstract: Information on geographic patterns of species genetic diversity is often needed to inform conservation strategies. Obtaining data over large geographic areas can be difficult, especially for rare or elusive species. Here, we explore the use of invertebrate‐derived DNA (iDNA) obtained from terrestrial leeches to assess genetic diversity of the Annamite striped rabbit Nesolagus timminsi, a little‐known and highly threatened lagomorph endemic to the Annamites ecoregion of Vietnam and Laos. We collected 4, 877 leeches pooled into 651 leech bulk samples from eight study areas across the northern and central Annamites. Using metabarcoding, we detected Annamite striped rabbit DNA in 11 leech bulk samples from five of the study areas. We amplified up to 3, 000 bp of six mitochondrial DNA loci of Annamite striped rabbit from nine of the 11 bulk samples. Haplotype network analyses showed five shared haplotypes among these samples. Phylogenetic trees constructed using maximum likelihood and Bayesian inference showed little geographic structuring among the Annamite striped rabbit populations across the five study areas. Our results provide information that can be directly used to inform planned ex situ conservation measures for the Annamite striped rabbit. We discuss our results within the context of using iDNA to noninvasively obtain data to assess species genetic diversity, and the potential of this approach to be applied to other species and systems. Abstract : We used invertebrate‐derived DNA (iDNA) obtained from terrestrial leeches to assess genetic diversity of the Annamite striped rabbit Nesolagus timminsi, a little‐known and highly threatened lagomorph endemic to the Annamites ecoregion of Vietnam and Laos. Our results provide evidence how iDNA can be used to noninvasively obtain data to assess species' genetic diversity.